Optimal Stimulation Protocol in a Bistable Synaptic Consolidation Model - Gastaldi, Chiara; Muscinelli, Samuel; Gerstner, Wulfram (Frontiers in Computational Neuroscience, 2019)
Synaptic changes induced by neural activity need to be consolidated to maintain memory over​ a timescale of hours. In experiments, synaptic consolidation can be induced by repeating a stimulation protocol several times. However, the effectiveness of consolidation depends crucially on the repetition frequency of the stimulations. Here we propose a simple mathematical model that allows to systematically study the interaction between the stimulation protocol and synaptic consolidation. We show the existence of optimal stimulation protocols in our model which, similarly to LTP experiments, depend on the repetition frequency of the stimulation. Our results show that the complex dependence of LTP on the stimulation frequency emerges naturally from a minimal model with only two bistable variables.